Corporate Investment Efficiency Under Beta Uncertainty - Nolvi, Aaro (My University, 2026)
Discounted cash flow analysis is the dominant approach to corporate capital budgeting, and the cost of equity that enters the discount rate is most commonly estimated with the Capital Asset Pricing Model. Within that framework, the risk-free rate and the market risk premium are shared by firms operating in the same environment, while the beta coefficient is firm-specific and must be estimated from historical returns. Beta is therefore the main channel through which estimation error enters the cost of equity, and imprecise estimates may distort the discount rates used to evaluate investment opportunities. While the consequences of cost-of-equity imprecision for investment have been documented for North American firms, little is known about whether the relationship holds in Europe, where capital allocation relies more heavily on bank-based intermediation and where market signals are assumed to play a smaller role. This thesis examines whether the precision of firm-level beta estimates is associated with corporate investment efficiency among large, publicly listed European firms. The study draws on asset pricing theory, capital structure theory, agency theory, and Tobin's Q-theory of investment to motivate the mechanism linking estimation precision to capital allocation. Investment efficiency is captured by Abnormal Investment, defined as the absolute residual from a model of capital investment on Tobin's Q, operating cash flow, asset growth, and lagged investment. Cost-of-equity precision is captured by Beta Precision, defined as the negative of the standard error of beta from a market model regression. The data are drawn from the component firms of a broad European equity index over a period spanning more than two decades, and the relationship is estimated using ordinary least squares, quantile, and directional specifications, supported by an extensive set of robustness tests. More precise beta estimates are found to be associated with significantly lower abnormal investment, and the result survives the inclusion of industry, year, and firm fixed effects, alternative risk models and estimation windows, firm-size partitions, and governance controls. The disciplining effect is concentrated in restraining overinvestment rather than in correcting underinvestment, and it is proportionally stronger than has been reported for North American firms. In contrast to the North American evidence, market-based growth signals appear unrelated to European investment. The findings indicate that cost-of-equity precision operates in Europe primarily as an internal capital-allocation discipline rather than through external market pressure, and that the quality of beta estimation is an economically meaningful input to corporate investment decisions rather than a purely technical detail.

Diskontatun kassavirran analyysi on yritysten investointilaskennan vallitseva menetelmä, ja sen diskonttauskoron keskeisin osatekijä, oman pääoman kustannus, arvioidaan yleisimmin Capital Asset Pricing -mallilla. Tässä viitekehyksessä riskitön korko ja markkinariskipreemio ovat yhteisiä samassa ympäristössä toimiville yrityksille, kun taas beta-kerroin on yrityskohtainen ja se on estimoitava historiallisista tuotoista. Beta on siten keskeisin kanava, jonka kautta estimointivirhe siirtyy oman pääoman kustannukseen, ja epätarkat estimaatit voivat vääristää investointimahdollisuuksien arvioinnis-sa käytettyjä diskonttauskorkoja. Vaikka oman pääoman kustannuksen epätarkkuuden vaikutukset investointeihin on dokumentoitu pohjoisamerikkalaisilla yrityksillä, on epäselvää, päteekö yhteys Euroopassa, jossa pääoman allokointi nojaa vahvemmin pankkivälitteiseen rahoitukseen ja jossa markkinasignaalien oletetaan olevan vähäisemmässä roolissa. Tämä tutkielma tarkastelee, onko yrityskohtaisten beta-estimaattien tarkkuus yhteydessä yritysten investointitehokkuuteen suurissa, julkisesti noteeratuissa eurooppalaisissa yrityksissä. Tutkimus pohjautuu arvopaperien hinnoitteluteoriaan, pääomarakenneteoriaan, agenttiteoriaan sekä Tobinin Q-investointiteoriaan, joiden avulla perustellaan estimointitarkkuuden ja pääoman allokoinnin välinen mekanismi. Investointitehokkuutta mitataan epänormaalilla investoinnilla, joka määritellään jäännöstermin itseisarvona mallista, jossa investointeja selitetään Tobinin Q:lla, liiketoiminnan rahavirralla, taseen kasvulla ja edellisen kauden investoinneilla. Oman pääoman kustannuksen tarkkuutta mitataan betan estimointitarkkuudella, joka määritellään markkinamalliregression beta-kertoimen keskivirheen vastalukuna. Aineisto koostuu laajan eurooppalaisen osakeindeksin yrityksistä yli kahden vuosikymmenen ajalta, ja yhteyttä estimoidaan pienimmän neliösumman, kvantiili- ja suuntaeritellyillä malleilla, joita täydennetään kattavilla robustisuustesteillä. Tarkempien beta-estimaattien havaitaan olevan yhteydessä merkitsevästi pienempään epänormaaliin investointiin, ja tulos säilyy toimiala-, vuosi- ja yrityskohtaisten kiinteiden vaikutusten, vaihtoehtoisten riskimallien ja estimointi-ikkunoiden, kokoluokittelun sekä hallinnointitapaa kuvaavien kontrollimuuttujien lisäämisen jälkeen. Kurinpitovaikutus keskittyy yli-investoinnin hillitsemiseen pikemmin kuin ali-investoinnin korjaamiseen, ja se on suhteellisesti voimakkaampi kuin pohjoisamerikkalaisilla yrityksillä on raportoitu. Toisin kuin pohjoisamerikkalaisessa aineistossa, markkinaperusteiset kasvusignaalit eivät näytä olevan yhteydessä eurooppalaisten yritysten investointeihin. Tulokset osoittavat, että oman pääoman kustannuksen tarkkuus toimii Euroopassa ensisijaisesti sisäisenä pääoman allokoinnin kurinpitomekanismina eikä ulkoisen markkinapaineen kautta, ja että beta-estimoinnin laatu on taloudellisesti merkittävä tekijä yritysten investointipäätöksissä eikä pelkkä tekninen yksityiskohta.
Keywords: investments; finance; BETA; agency theory; financial markets; investment assets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance